2010
DOI: 10.1002/stem.296
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Generated from APP/APLP1/APLP2 Triple Knockout Embryonic Stem Cells Behave Normally in Vitro and in Vivo: Lack of Evidence for a Cell Autonomous Role of the Amyloid Precursor Protein in Neuronal Differentiation

Abstract: Alzheimer's disease amyloid precursor protein (APP) has been implicated in many neurobiologic processes, but supporting evidence remains indirect. Studies are confounded by the existence of two partially redundant APP homologues, APLP1 and APLP2. APP/APLP1/APLP2 triple knockout (APP tKO) mice display cobblestone lissencephaly and are perinatally lethal. To circumvent this problem, we generated APP triple knockout embryonic stem (ES) cells and differentiated these to APP triple knockout neurons in vitro and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 61 publications
2
29
1
Order By: Relevance
“…These findings are further supported by previous results from Taylor et al who showed a requirement for APPsa for in vivo LTP in rats employing infusion of a-secretase inhibitor or recombinant APPsa and demonstrated that exogenously applied APPsa facilitates evoked NMDAR currents at the postsynaptic site (Taylor et al 2008). The requirement of APP and APLP2 for normal CNS function contrasts, however, with the normal differentiation and electrophysiological properties of cultured neurons lacking all three APP family members (Bergmans et al 2010) and highlights the importance to study APP family functions in the living organism.…”
Section: In Vivo Analysis Of App/aplp Functional Domainssupporting
confidence: 84%
“…These findings are further supported by previous results from Taylor et al who showed a requirement for APPsa for in vivo LTP in rats employing infusion of a-secretase inhibitor or recombinant APPsa and demonstrated that exogenously applied APPsa facilitates evoked NMDAR currents at the postsynaptic site (Taylor et al 2008). The requirement of APP and APLP2 for normal CNS function contrasts, however, with the normal differentiation and electrophysiological properties of cultured neurons lacking all three APP family members (Bergmans et al 2010) and highlights the importance to study APP family functions in the living organism.…”
Section: In Vivo Analysis Of App/aplp Functional Domainssupporting
confidence: 84%
“…Previously, we analysed neurons generated in vitro from triple ko APP/APLP1/APLP2 embryonic stem cells (Bergmans et al, 2010) and did not find any obvious phenotype. This prompted us to further investigate the role of APP gene family in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…APP/APLP2 and APLP1/APLP2 double knockout mice demonstrate a reduced viability similar to the triple knockout model and the APP/ APLP2 knockout mice suffer from defective neuromuscular synapses (9). Surprisingly, triple knockout neurons derived from triple knockout embryonic stem cells did not show macroscopic abnormalities (10). At the molecular level, a decreased expression of the vesicular glutamate transporter 2 was detected in glutamatergic neurons differentiated from APP/APLP2 knockout embryonic stem cells (11).…”
mentioning
confidence: 83%